(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Steatohepatitis is an inflammation of the hepatic parenchyma that has aggravated the fatty transformation of the liver. The disease is asymptomatic for a long time. It can manifest itself as abdominal discomfort, pain in the right hypochondrium, dyspepsia, hepatomegaly, asthenic syndrome. It is diagnosed using biochemical blood analysis, ultrasound, static scintigraphy, liver fibroscopy, biopsy histology. Hepatoprotectors, biguanides, insulin sensitizers, anorexigenic drugs, statins, fibrates are used for treatment. It is possible to perform gastroplasty to correct weight. In case of severe liver failure, organ transplantation is necessary.